Pengaruh Perputaran Modal Kerja, Perputaran Piutang, Dan Perputaran Total Aset Terhadap Profitabilitas: Studi Kasus Pada Perusahaan Sub Sektor Kehutanan Dan Kertas Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2022 - Kaula Desma Sari; Ahmad Idris; Taufik Akbar (Jurnal Riset dan Inovasi Manajemen, 2024)
This research aims to analyze and determine how the effect of working capital turnover, receivable turnover, and total asset turnover on profitability (Return on Asset) in forestry and paper sub sector companies listed on Indonesia Stock Exchange in 2018-2022. This research is quantitative research using secondary data which is taken from the company’s annual financial reports. Purposive sampling is used in this research to take samples. The analytical techniques used are panel data regression analysis with the help of Eviews 9 software. Based on the research that has been carried out, it can be concluded that partially the working capital turnover and total asset turnover have no effect on profitability, whereas receivable turnover has an effect on profitability. Simultaneously, working capital turnover, receivable turnover, and total asset turnover had an effect on profitability in forestry and paper sub sector companies listed on the Indonesia Stock Exchange in 2018-2022.